1988
DOI: 10.1111/j.1471-4159.1988.tb01816.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2‐(4‐Phenylpiperidino)cyclohexanol (AH 5183) on the Veratridine‐Induced Increase in Acetylcholine Synthesis by Rat Hippocampal Tissue

Abstract: The intent of this study was to determine whether the drug 2-(4-phenylpiperidino)cyclohexanol (AH 5183 or vesamicol) might inhibit the veratridine-induced increase in acetylcholine (ACh) synthesis by reducing the veratridine-induced activation of a detergent-soluble choline-O-acetyltransferase (EC 2.3.1.6; ChAT) fraction associated with a vesicle-bound store of ACh. When minces of rat hippocampal tissue were loaded with [14C]choline and subsequently depolarized with veratridine, an increase in the synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In the present study, vesamicol maximally suppressed the release of ACh by 52-55%, an effect that saturated at 3-10 HMofdrug. Comparably, in vitro studies have shown that similar or higher concentrations of vesamicol reduce the K+ or veratridine evoked release of ACh by 44-75% in cortical synaptosomes and slices (10 pM, Otero et al, 1985;Jope and Johnson, 1985), by up to 79% in mouse forebrain minces (17 pM, Carroll, 1985), by 77% in rat hippocampal slices (75 nM, Carroll and Ivy, 1988), and by as much as 90% in rat striatal slices (10 pM, R%n$ and Collier, 1986). Because the anticholinergic effect of vesamicol is stimulus dependent (Marshall, 1970;Whitton et al, 1986;Van der Kloot, 1986), the slightly greater efficacy of vesamicol observed in vitro may be related to the high depolarizing concentrations of K+ (30-60 mM) routinely applied in these studies.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, vesamicol maximally suppressed the release of ACh by 52-55%, an effect that saturated at 3-10 HMofdrug. Comparably, in vitro studies have shown that similar or higher concentrations of vesamicol reduce the K+ or veratridine evoked release of ACh by 44-75% in cortical synaptosomes and slices (10 pM, Otero et al, 1985;Jope and Johnson, 1985), by up to 79% in mouse forebrain minces (17 pM, Carroll, 1985), by 77% in rat hippocampal slices (75 nM, Carroll and Ivy, 1988), and by as much as 90% in rat striatal slices (10 pM, R%n$ and Collier, 1986). Because the anticholinergic effect of vesamicol is stimulus dependent (Marshall, 1970;Whitton et al, 1986;Van der Kloot, 1986), the slightly greater efficacy of vesamicol observed in vitro may be related to the high depolarizing concentrations of K+ (30-60 mM) routinely applied in these studies.…”
Section: Discussionmentioning
confidence: 97%
“…Male Sprague-Dawley rats were decapitated, and the brains were quickly removed and placed into an ice-cold normal Krebs solution (pH 7.4) vigorously bubbled with 95% 0 2 / 5% COz as described previously (Carroll and Ivy, 1988). In the case of the zinc experiments, the brains were placed into a 15 mM Tris buffer of the following composition: NaCI, 157 mM, KCl, 5.7 mM; MgCl2.6HzO, 1.5 mM; CaC12, 2.5 d, glucose, 1 1 .…”
Section: Preparation Of Hippocampal Mincesmentioning
confidence: 99%
“…Hippocampal minces (each incubated sample contained two hippocampi of -160-200 mg) were incubated in a normal Krebs solution (pH 7.4) for 30 rnin at 30°C in the absence or presence of varying concentrations of PLC from B. cereus (0.125, 1.25, and 12.5 U/ml). The activities ofChAT, AChE, and LDH and the amount of protein in the release media were determined as previously described (Benishin and Carroll, 1983;Carroll and Ivy, 1988).…”
Section: Release Of Chat By Plcmentioning
confidence: 99%
See 2 more Smart Citations